Influence of dielectric layers and thermal load on LeTID - Winter, Clemens; Zuschlag, Annika; Skorka, Daniel; Hahn, Giso (My University, 2018)
Light and elevated temperature induced degradation (LeTID) is observed for multicrystalline (mc) Si passivated emitter and rear cell (PERC) solar cells, strongly limiting solar cell parameters under operation conditions. In this contribution, we investigate the effect of surface passivation layer being present during the firing step based on lifetime samples. The LeTID effect is only observed if the surface passivation layer is present during the firing step. Samples without firing step show no LeTID. A re-passivation of the surface significantly changes the LeTID effect, showing that the whole sample treatment, temperature load and hydrogen content of a sample has to be taken into account investigating and evaluating LeTID.
Keywords: 530